The Implementation of Technology Based Differentiated Instruction Toward Teachers’ Interest - Maharani, Made Diva; Juniarta, Putu Adi Krisna; Agustini, Dewa Ayu Eka (International Journal of Language and Literature, 2025)
There is low teacher interest in implementing technology-based differentiated learning. A lack of understanding and skills in utilizing technology to support differentiated learning is a major obstacle to optimizing the teaching and learning process. This research aims to observe the implementation of technology based differentiated learning in english language learning and to find out teachers' interest in using technology based differentiated learning in english language learning. This research uses exploratory sequential mix method. Qualitative data was obtained by using an observation sheet to observe the application of technology based differentiated learning in english learning and quantitative data was obtained by using google form to find out teachers' interest when technology based differentiated learning was applied in english learning. There are three aspects used in the observation sheet, namely content, process, product. The questionnaire used consisted of 23 items that were adjusted to the research. The subjects of this study were three eleventh grade english teachers. This study found that technology based differentiated learning is implemented in english learning and revealed that teachers have a high interest in english learning that implements technology based differentiated learning. This study emphasizes the importance of teachers in implementing technology based differentiated teaching in english language learning.